2017
DOI: 10.1111/aji.12650
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy regulation of physiological and pathological processes in the female reproductive tract

Abstract: Autophagy is a ubiquitous cell recycling pathway that delivers cytoplasmic constituents to the lysosome and is essential for normal cellular function. Autophagic activity is up‐regulated under physiological conditions as well as stressful conditions such as nutrient deprivation, oxidative stress, hypoxia, inflammation, and infection. Thus, it is essential to regard the functional importance of the pathway and its components in a given tissue context. Here we review what is known about the involvement of autoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…Our findings that cortisol degrades COL1A1 and COL3A1 through lysosome and proteasome pathways, respectively, appear to reconcile with previous studies showing that both ubiquitin-proteasome and autophagic lysosome pathways are activated during ROM (Cao et al 2017, Zhao et al 2017. Although collagens I and III comprise the backbone of the mesenchymal structure of the compact layer in the amnion, they may differ slightly in their functional roles in ECM remodeling.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings that cortisol degrades COL1A1 and COL3A1 through lysosome and proteasome pathways, respectively, appear to reconcile with previous studies showing that both ubiquitin-proteasome and autophagic lysosome pathways are activated during ROM (Cao et al 2017, Zhao et al 2017. Although collagens I and III comprise the backbone of the mesenchymal structure of the compact layer in the amnion, they may differ slightly in their functional roles in ECM remodeling.…”
Section: Discussionsupporting
confidence: 88%
“…The exact mechanisms of the mild shedding of the EGX in healthy ovulatory women and the tremendous shedding observed in pregnancy is presently unknown; however, it can be assumed that inflammatory processes may be responsible factors . It has already been demonstrated that endotoxin, ischemia reperfusion, atrial natriuretic peptide, BNP, tumor necrosis factor‐alpha, and activated leukocytes, which can induce the expression of heparanases and oxygen radicals, can lead to a destruction of the EGX.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is a non-apoptotic form of over-activated programmed cell death [27,28]. Autophagy plays an indispensable role in early embryonic development, which is often associated with abortion, preeclampsia, intrauterine growth restriction and other pathological pregnancies [29][30][31]. In this study, we detected the level of autophagy in villi of RSA patients was significantly lower than that of normal abortion patients.…”
Section: Discussionmentioning
confidence: 64%